2017
DOI: 10.5312/wjo.v8.i9.741
|View full text |Cite
|
Sign up to set email alerts
|

Hernia mesh prevent dislocation after wide excision and reconstruction of giant cell tumor distal radius

Abstract: Giant cell tumor (GCT) remains as major health problem. GCT which located at the lower end of the radius tends to be more aggressive. Wide excision and reconstruction of the wrist in stage 3 of distal radius GCT lesion is an optimal modality to prevent tumor recurrence. However, dislocation often occurs as its complication. We are reporting patient with GCT of distal radius treated with wide excision and reconstruction using nonvascularized fibular graft and the addition of hernia mesh. Circumferential non-abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The management of this lesion in distal radius had been further modified with hernia mesh to prevent dislocation to prevent dislocation. 24 Osteoblastic osteosarcoma is an osteosarcoma dominated by malignant osteoblast proliferation with prominent osteoid matrix and weaved in between neoplastic cells. 7, 16 Radiograph appearance in this study showed that all osteoblastic subtypes commonly accompanied by bone destruction, dominantly permeative type, although in some can be found geographic and moth eaten.…”
Section: Original Articlementioning
confidence: 99%
“…The management of this lesion in distal radius had been further modified with hernia mesh to prevent dislocation to prevent dislocation. 24 Osteoblastic osteosarcoma is an osteosarcoma dominated by malignant osteoblast proliferation with prominent osteoid matrix and weaved in between neoplastic cells. 7, 16 Radiograph appearance in this study showed that all osteoblastic subtypes commonly accompanied by bone destruction, dominantly permeative type, although in some can be found geographic and moth eaten.…”
Section: Original Articlementioning
confidence: 99%
“…LARS® has been proven to enhance soft tissue reconstruction and ameliorate postoperative functional outcomes in limb salvage surgery for humeral, femoral, and tibial tumors; however, investigations using a synthetic mesh in tumor resection and reconstruction of the distal radius are extremely limited 13,14,20–22 . To the best of our knowledge, the successful application of a hernia mesh wrapping an FA has only been introduced in a case report 23 . Three‐dimensional printing technology has promoted enormously the development of basic orthopedic investigations in the past decade 24–27 .…”
Section: Introductionmentioning
confidence: 99%
“…13,14,[20][21][22] To the best of our knowledge, the successful application of a hernia mesh wrapping an FA has only been introduced in a case report. 23 Three-dimensional printing technology has promoted enormously the development of basic orthopedic investigations in the past decade. [24][25][26][27] However, relatively few studies based on this emerging technology have been conducted in clinical musculoskeletal oncology, in which major investigations focus on the reconstruction of the spine, pelvis and diarthrosis in the lower extremities.…”
Section: Introductionmentioning
confidence: 99%